Eucharystia jako centrum celebracji chrześcijańskiej w ujęciu katechetycznej szkoły aleksandryjskiej - Marian Zając (Vox Patrum, 2012)
In connection with noticed today decrease of meaning and number of participants of the Eucharistic celebration and disappearance its common and conscious experiences, author of the article in searching inspirations to solve this situation appeals to the Early Christian tradition of the Alexandrian Catechetical School of the III-V century. In this, exactly, school belief in real presence of Christ in the celebration of the Holy Eucharist and awareness of its consequences was a key value. The faced problem is figured out at the three chapters: 1. Eucharist – a celebrated mystery. 2. The Alexandrian Catechetical School in work for modern school of Eucharist (talked through multiple statements, science about Eucharist of aspect of real presence, sacrifice and fruits of experience four most famous its leaders: Clement of Alexandria, Origen of Alexandria, Athanasius of Alexandria and Cyril of Alexandria); 3. The Eucharist and catechetical mission.